(untitled) (Bangladesh Journal of Pharmacology, 2015)
The present study was commenced to evaluate the anti-arthritic effect of 70% methanol extract and n-butanol and aqueous fractions of Berberis calliobotrys using both in vitro and in vivo arthritis models. Extract and fractions were investigated in vitro for inhibition of protein (bovine serum and egg albumin) denaturation and human red blood cell membrane stabilization. In vivo anti-arthritic activity of extract and fractions at 50, 100 and 200 mg/kg was assessed using turpentine oil and formaldehyde-induced arthritis, while, 200 mg/kg dose was evaluated against complete Freunds adjuvant-induced arthritis. B. calliobotrys produced significant (p<0.001) dose dependent inhibition of protein denaturation and human red blood cell membrane stabilization. In turpentine oil, formaldehyde and complete Freunds adjuvant-induced arthritis models, B. calliobotrys significantly (p<0.001) reduced joint and paw swelling. B. calliobotrys markedly improved body weight, hematology profile, radiological and histopathological parameters in complete Freunds adjuvant model. It could be concluded that B. calliobotrys holds anti-arthritic potential, supporting its traditional use in treatment of rheumatoid arthritis.